2012
DOI: 10.1055/s-0039-1698973
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temperature change on fluoride uptake from a mouthrinse by enamel specimens

Abstract: Objective: The aim of this study was to examine the effect of temperature on fluoride uptake by enamel specimens from a 0.05% NaF-fluoridated mouthrinse (Oral-B Advantage; Oral-B Laboratories, Newbridge, UK).Methods: Enamel specimens were prepared from extracted human maxillary central incisors. A fluoride-specific ion electrode was used to measure the uptake from a 2 ppm fluoride solution containing 50.0 mL of distilled water, total ion strength adjustment buffer, and fluoridated rinse at 3 different temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Few studies reported the temperature-dependent fluoride uptake by the enamel. Baglar et al [25] found in their study that fluoride uptake by enamel from NaF mouth rinse increased by preheating the mouth rinse from 25°C to 37°C and 43°C, and the fluoride concentration in the mouth rinse was decreased after 1 min to be 2, 1.79, and 1.25 ppm, respectively. Barrancos [26] also reported this finding when the room temperature was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies reported the temperature-dependent fluoride uptake by the enamel. Baglar et al [25] found in their study that fluoride uptake by enamel from NaF mouth rinse increased by preheating the mouth rinse from 25°C to 37°C and 43°C, and the fluoride concentration in the mouth rinse was decreased after 1 min to be 2, 1.79, and 1.25 ppm, respectively. Barrancos [26] also reported this finding when the room temperature was increased.…”
Section: Discussionmentioning
confidence: 99%
“…1 Availability and stability of fluoride in dentifrices are basic requirements for effectiveness against tooth decay. 2,3 Fluoride ions can inhibit Eur J Dent 2020;14:38-44 the production of bacterial acids in dental plaque due to the influx of hydrogen fluoride into bacterial cells, and the dissociation to the H + and Fions in the cytoplasm. 4 For caries control, dentifrice formulation should contain a minimum of 1000 parts per million (ppm) fluoride, which must be in a soluble form to impart the anticaries effect.…”
Section: Introductionmentioning
confidence: 99%
“…7 Dentifrice composition plays a crucial role in disabling free fluoride ions, which may lead to creation of a low-solubility product with a diminished anticaries outcome. 2,3 Currently, there are no regulations to specify how much of total fluoride should be maintained in a dentifrice formulation. 5 There has been a growing interest in the use of "smart" bioactive materials (i.e., amorphous calcium phosphate, hydroxyapatite, bioactive glass, etc.)…”
Section: Introductionmentioning
confidence: 99%